MENINGKATKAN PENGETAHUAN: PENGARUH BUDAYA PANTANGAN MAKANAN PADA IBU MENYUSUI TERHADAP KEJADIAN STUNTING DI MASYARAKAT - Amri Yasir, Lalu; Layla Salfarina, Anna; Nurul Hidayati, Baiq; Putri Rusiana, Harlina; Ilham, Ilham; Isnani Hertin, Putri; Dwi Arika Martiana, Bq. (Stikes Yarsi Mataram, 2024)
The culture of food taboos for breastfeeding mothers is still strong in society and limits nutritional intake for breastfeeding mothers, which causes nutritional deficiencies in babies and toddlers. This is the basis for the Stikes Yarsi Mataram Service Team to carry out community service in the form of health education. This activity aims to increase public knowledge regarding the importance of meeting nutritional needs of breastfeeding mothers as a measure to prevent stunting in toddlers. The methods applied include the development of counseling materials, program socialization, small group counseling, and individual counseling and evaluation. The results showed a significant increase from 16.7% to 66.7% of breastfeeding mothers' knowledge in the good category. There is an increase in public knowledge about the importance of nutritional intake and the negative impact of the culture of food taboos, as well as behavioural changes in nutrition and balanced nutrition for breastfeeding mothers. The importance of understanding the need for balanced nutrition for breastfeeding mothers in preventing stunting is a shared responsibility in realising a healthy and strong generation of the nation.